Social Correlates of Official Index Crime Rates for States, SMSAs, and Cities (United States): A Macro-Level Dataset for 1950, 1960, 1970, and 1980 - Cohen, Lawrence E. ([Verlag nicht ermittelbar], 1999)
These data provide official index crime rates and social and economic indicators of crime rates at three levels of aggregation (city, state, and metropolitan areas) for four decennial years: 1950, 1960, 1970, and 1980. Information is provided on Uniform Crime Reports murder, rape, robbery, aggravated assault, burglary, larceny theft, and vehicle theft rates per 100,000 population. Social and economic indicators include percent black population, percent divorced males, the mean and median family incomes, families below the poverty line, and percent unemployed for each area. The availability of the data for the crime rates in 1980 determined the geographic locations included in the data collection. Data from earlier years do not exist for all geographic locations for which data were available in 1980.